The Influence of Business Ethics, Organizational Governance, and Corporate Social Responsibility on the Financial Performance of Companies Listed on the Indonesia Stock Exchange - Stephanie, Stephanie; Ria Murhadi, Werner (Journal of Economics and Business UBS, 2023)
Sustainability issue nowadays requires companies in Indonesia to act strategically and not only focus on financial performance, but also social and environmental aspects. Corporate social responsibility is seen as an obligate and one way to comply with the business ethics value as generally required by society. However, the differences in the company’s stakeholders’ needs could cause variation of corporate governance system, which sometimes does not follow the ethics value. This research aims to look over the effect of ethics (generally) to corporate governance practices and implementation of corporate social responsibility in Indonesia, also towards the company’s financial performance. The sample of this research is the companies listed in the IDX80 index of Bursa Efek Indonesia. The data collection technique used is the purposive sampling method and data collected will be analyzed using linear regression method. This research proved that ethics affecting the corporate governance system and corporate social responsibility practices, but there’s no prove that corporate governance system and corporate social responsibility affect the corporate financial performance.